Dampak Flash Sale Shopee Terhadap Perilaku Impulsive Buying Konsumen - Hasna Fitri; Didin Hadi Saputra; Agus Safari (CV. Dalle’ Deceng Abeeayla, 2026)
This study aims to determine the effect of flash sales on impulsive buying among Shopee users. This study used a quantitative approach with primary data sources obtained through questionnaires distributed using Google Forms. The study population was Shopee users, while the sample consisted of 100 respondents, students at Nahdlatul Wathan University, Mataram. The sampling technique used non-probability sampling with a purposive sampling method. Respondents were aged 18–24, had used Shopee before, and had utilized the flash sale feature. Variable measurements were performed using a five-point Likert scale. Data analysis was performed using Jamovi software through validity tests, reliability tests, and a One-Sample t-Test. The development of information technology and the internet has driven the rapid growth of e-commerce, one of which is through the Shopee platform. Various digital promotional strategies implemented by Shopee, such as flash sales, have proven effective in attracting consumers' attention and encouraging them to make purchases. Flash sales are promotional programs that offer products at discounted prices for a limited time and in limited quantities, creating a sense of urgency and encouraging consumers to make quick purchases. This situation has the potential to trigger impulsive buying behavior, namely purchases made spontaneously without prior planning. Research shows that Shopee's Flash Sale program is an effective digital marketing strategy in increasing consumer impulsive buying behavior and influencing purchasing decisions on the e-commerce platform.